Consumption and account balances in crises: Have we neglected cognitive load? - Tiziana Assenza; Alberto Cardaci; Michael Chaliasos (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2023)
The complexities of geopolitical events, financial and fiscal crises, and the ebb and flow of personal life circumstances can weigh heavily on individuals' minds as they make critical economic decisions. To investigate the impact of cognitive load on such decisions, we conducted an incentivized online experiment involving a representative sample of 2,000 French households.. The results revealed that exposure to a taxing and persistent cognitive load significantly reduced consumption, particularly for individuals under the threat of furlough, while simultaneously increasing their account balances, particularly for those not facing such employment uncertainty. These effects were not driven by supply constraints or a worsening of credit constraints. Instead, cognitive load primarily affected the optimality of the chosen policy rules and impaired the ability of the standard economic model to accurately predict consumption patterns, although this effect was less pronounced among college-educated subjects.
Keywords: G5; C9; D15; D91; 330; consumption; saving; borrowing; cognitive load; online experiments; RCT; crises; furlough